Transmitter and receiver polarisation optimisation design for target. Issue 21 (7th October 2019) - Hu, Kexiao; Liu, Zhiwen; Shi, Shuli; Xu, Yougen
Abstract : In radar systems, transmitting and receiving waveforms with different polarisations benefit to acquire complete information about the target and its environment, ensuring significant enhancement of the radar's performance. Here, the authors consider the optimisation problem of jointly designed transmitter and receiver (TR) polarisation from the view of target scattering estimation. Under the condition that the target and clutter scattering covariance is known as a prior, they first use sequential linear minimum mean square error estimation to obtain the target scattering matrix and then optimise the sensing vector, which contains the polarisation information under the constraint of minimising the mean square error. The mentioned problem can be solved by eigenvector decomposition. Then, a method to get the TR polarisation parameters is provided. Finally, they use numerical simulations to show the advantage of the proposed methods.